1975
DOI: 10.1002/aic.690210313
|View full text |Cite
|
Sign up to set email alerts
|

A generalized thermodynamic correlation based on three‐parameter corresponding states

Abstract: feed to a typical coal processing fluidized bed (Skinner, 1970) ; fine particles in the distribution have a considerable effect on the calculation. Similarly, it is not clear at present exactly how dp should be specified in applying the correlation for jet penetration depth to a bed with a wide range of particle sizes. ACKNOWLEDGMENTThis work was carried out at the Research Laboratories of Westinghouse Electric Corporation and was partially sponsored by the Office of Coal Research. The author wishes to thank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
702
2
10

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,448 publications
(752 citation statements)
references
References 37 publications
11
702
2
10
Order By: Relevance
“…All experiments from this series were carried out with the reservoir evacuated to a pressure of less than 1 mbar. Thermodynamic properties such as liquid and vapour densities were estimated from the Lee & Kesler (1975) The second set of experiments, the 'isothermal series', was designed to investigate the subsonic branch of the Rankine-Hugoniot curve. To achieve this goal, the liquid was exposed to decreasing values of the reservoir pressure at a fixed liquid temperature (230 • C).…”
Section: Resultsmentioning
confidence: 99%
“…All experiments from this series were carried out with the reservoir evacuated to a pressure of less than 1 mbar. Thermodynamic properties such as liquid and vapour densities were estimated from the Lee & Kesler (1975) The second set of experiments, the 'isothermal series', was designed to investigate the subsonic branch of the Rankine-Hugoniot curve. To achieve this goal, the liquid was exposed to decreasing values of the reservoir pressure at a fixed liquid temperature (230 • C).…”
Section: Resultsmentioning
confidence: 99%
“…If these parameters are not available, they can be approximated from species with similar molecular structures. The next step was to calculate the acentric factor, ω, using the Lee-Kesler vapor-pressure relation [74]: The polarizability, α, of a molecule describes the tendency of a molecule's charge distribution to be distorted by the presence of an electric field from a nearby ion or dipole. This property can be calculated using an empirical additive formula presented by Bosque and Sales [76] that allows the estimation of polarizability from the molecular formula of hydrocarbons:…”
Section: Transport Propertiesmentioning
confidence: 99%
“…With the advent of cheaper and faster computers, Lee et al [6] suggested replacing the derivative in the Taylor series with its finite difference:…”
Section: Corresponding-states Principlementioning
confidence: 99%
“…Among the different models for the estimation of speeds of sound, the corresponding-states theory, namely the Lee-Kesler approach [6] has proved to be one of the most accurate models [7][8][9], although some large deviations have been recently found for the heavier n-alkanes [9].…”
Section: ρ (T P) = ρ (P Atm T ) +mentioning
confidence: 99%